Perancangan dan Pengembangan Produk “Mesin Penggiling Tahu pada Pabrik Tahu dengan Metode Quality Function Deployment (QFD)” - Jovita, Anjani; Mustofani, Muhammad Mikoriza; Ihsan, Tiaradia (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The Indonesian tofu industry faces challenges in the soybean grinding stage, which is still dominated by small-scale machines with limited capacity, poor grinding quality, and low energy efficiency. These constraints reduce the productivity and competitiveness of micro, small, and medium enterprises (MSMEs). This study aims to design a more efficient tofu grinding machine that meets user needs by applying the Quality Function Deployment (QFD) method. Using a descriptive approach with quantitative support, consumer needs (Voice of Customer) were identified, translated into technical responses, and analyzed through the House of Quality (HoQ) to determine technical priorities. Results show that consumers demand large production capacity, smooth grinding results, energy efficiency, durability, and easy maintenance. The highest-priority technical responses include high-power motors, stainless steel piping, and large-capacity grinding tubes.